2005
DOI: 10.3138/jvme.32.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing an Assessment Method to Evaluate a Virtual Canine Anatomy Program

Abstract: A computer-based anatomy program, Virtual Canine Anatomy: The Head, was incorporated into a first-year veterinary dissection laboratory two years ago to address challenges inherent in the traditional pedagogical approach. The program uses specimen photographs, QuickTime Virtual Reality, and interactive features to help students study the dissection, osteology, and radiology of the canine head. Photographs of each phase of dissection are displayed in the program, along with dissection instructions. Students can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
4
19
0
3
Order By: Relevance
“…Survey questions were developed following the same principles as in assessing another CAL education tool by Linton et al, 2005 [39] and were created to address six central themes of investigation: What is the participant’s general attitude toward CAL and the IVALA™ program?What is the perceived educational value of CAL and the IVALA™ program in relation to other learning resources?What effect did IVALA™ have on the laboratory dissection experience?Was the accuracy, fidelity, and content of IVALA™ suitable for this anatomy course?Was the IVALA™ program user friendly?Was the IVALA™ program beneficial to anatomic education? …”
Section: Methodsmentioning
confidence: 99%
“…Survey questions were developed following the same principles as in assessing another CAL education tool by Linton et al, 2005 [39] and were created to address six central themes of investigation: What is the participant’s general attitude toward CAL and the IVALA™ program?What is the perceived educational value of CAL and the IVALA™ program in relation to other learning resources?What effect did IVALA™ have on the laboratory dissection experience?Was the accuracy, fidelity, and content of IVALA™ suitable for this anatomy course?Was the IVALA™ program user friendly?Was the IVALA™ program beneficial to anatomic education? …”
Section: Methodsmentioning
confidence: 99%
“…Linton et al found that students and faculty expressed positive attitudes toward the program. They also found that it increased dissection efficiency (Linton et al 2005). Prior to its implementation, instructors overseeing dissection spent most of their time identifying basic structures for students and students spent a significant amount of time waiting for instructor assistance and relying on textbooks.…”
Section: Simulation Softwarementioning
confidence: 99%
“…Linton found that students and faculty alike expressed a strong degree of satisfaction with the program: "Faculty praised the program as a strong visual aid and self-paced study guide for students. Some instructors indicated that the application gave them more opportunities to discuss higher-level issues with the students such as structure functions and relationships" (Linton et al 2005). Students gave the application high ratings on all seven criteria that were employed in the study: general attitude toward the program, educational needs met, dissection assistance provided, increase in overall confidence, appropriate content for academic level, efficient use of laboratory time, and how user-friendly the program was.…”
Section: Simulation Softwarementioning
confidence: 99%
“…• superior understanding of complex biological processes (specifically, interactions between intracellular molecules and their spatial relationships within cells, Buchanan et al, 2005), and of systemic pathology (Hines et al, 2005); rapid access to relevant anatomical views such as radiographs, and increased learning efficiency (Linton et al, 2005); • enhanced preparedness for laboratories (Howe et al, 2005), and even, on occasion, increased realism of the laboratory experience (Modell et al, 2002); • increased examination results (parasitology, Pinkney et al, 2001;anaesthesiology, Modell et al, 2002 andanatomy, Josephon andMoore, 2006); • decreased student stress (Holmberg et al,1993), increased student satisfaction (Erickson and Clegg, 1993;Hines et al, 2005;Howe et al, 2005) and confidence (Linton et al, 2005), including when coping with complex clinical problems (Modell et al, 2002); • enhanced student information retrieval and communication abilities, improved student attitudes towards computers, and increased employer perception of computer literacy (Waldhalm and Bushby, 1996); • facilitation of ongoing undergraduate and postgraduate learning (Whithear et al, 1994;Dhein and Memon, 2003); • increased teaching efficiency and decreased costs (Rudas et al, 1993;Dhein and Memon, 2003);…”
Section: Veterinary Disciplinesmentioning
confidence: 99%